Soft-donor dipicolinamide derivatives for selective actinide(iii)/lanthanide(iii) separation: the role of S- vs. O-donor sites. Issue 17 (8th February 2019) - Lehman-Andino, Ingrid; Su, Jing; Papathanasiou, Konstantinos E.; Eaton, Teresa M.; Jian, Jiwen; Dan, David; Albrecht-Schmitt, Thomas E.; Dares, Christopher J.; Batista, Enrique R.; Yang, Ping; Gibson, John K.; Kavallieratos, Konstantinos
Abstract : A dithiopicolinamide analog selectively extracts Am(iii ) over Eu(iii ) under acidic conditions. Abstract : Selectivity for An(iii ) vs. Ln(iii ) binding and extraction using dipicolinamide analogs containing the CO vs. CS groups was investigated in solution and the gas-phase, and by DFT calculations. The results show higher selectivity for complex formation and extraction for Am(iii ) vs. Eu(iii ) for the softer dithioamide vs. the diamide ligand, while in CH3 CN the diamide binds more strongly than the thioamide to several Ln(iii ), forming 1 : 1 complexes.